Torneträsk Tree Ring MXD Temperature Reconstruction AD 500-2004 - Håkan Grudd (Stockholm University, 2015)
A temperature reconstruction for the period AD 500-2004 based on tree-ring maximum density (MXD) at Tornetrask in northern Sweden
Keywords: Paleoclimatology; Physical Geography; Climate Science; Environmental Science; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap; Physical Geography; Naturgeografi